Maximal power training induced different improvement in throwing velocity and muscle strength according to playing positions in elite male handball players - Cherif, M; Chtourou, H; Souissi, N; Aouidet, A; Chamari, K (Biology of Sport, 2016)
This study was designed to assess the effect of strength and power training on throwing velocity and muscle strength in handball players according to their playing positions. Twenty-two male handball players were assigned to either an experimental group (n=11) or a control group (n=11) (age: 22.1 ± 3.0 years). They were asked to complete (i) the ball throwing velocity test and (ii) the one-repetition maximum (1-RM) tests for the half-back squat, the pull-over, the bench press, the developed neck, and the print exercises before and after 12 weeks of maximal power training. The training was designed to improve strength and power with an intensity of 85-95% of the 1RM. In addition to their usual routine handball training sessions, participants performed two sessions per week. During each session, they performed 3-5 sets of 3-8 repetitions with 3 min of rest in between. Then, they performed specific shots (i.e., 12 to 40). Ball-throwing velocity (p<0.001) was higher after the training period in rear line players (RL). The training programme resulted in an improvement of 1RM bench press (p<0.001), 1RM developed neck (p<0.001) and 1RM print (p<0.001) in both front line (FL) and RL. The control group showed a significant improvement only in ball-throwing velocity (p<0.01) and 1RM bench press (p<0.01) in RL. A significantly greater improvement was found in ball-throwing velocity (p<0.001), 1RM bench press (p<0.001), and 1RM half-back squat exercises in players of the central axis (CA) compared to the lateral axis (LA) (p<0.01). The power training programme induced significantly greater increases in ball-throwing velocity and muscle strength in FL than RL and in CA than LA axis players.